Polyvinyl acetal resin
By adjusting the structural parameters of polyvinyl acetal resin, the problems of uneven tensile strength and insufficient stress at break point of ceramic green sheets are solved, and the electrical characteristics and productivity of ceramic capacitors are improved.
Patent Information
- Application Number
- CN202380040608.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-27
AI Technical Summary
The existing polyvinyl acetal resins have problems of uneven tensile strength and insufficient stress at break point when making ceramic green sheets, especially during the thin layering of ceramic green sheets, which affects the improvement of electrical characteristics.
Adjust the peak integral ratio of the methmethyl C atoms in the triple unit by 13C-NMR measurement, and combine high-performance liquid chromatography and viscometer to ensure the weight average molecular weight, hydroxyl amount and acetyl of the polyvinyl acetal resin The base amount is within a specific range, and resins with uniform tensile strength and high break point stress are prepared.
The uniform tensile strength and high break point stress of the ceramic green sheet are achieved, the time-dependent viscosity stability and productivity of the ceramic slurry are improved, and the electrical characteristics of the ceramic capacitor are improved.
Smart Images

Figure CN119213038A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polyvinyl acetal resin. Background Art
[0002] In recent years, electronic components mounted in various electronic devices have been miniaturized and laminated, and laminated electronic components such as multilayer circuit boards, laminated coils, and laminated ceramic capacitors have been widely used.
[0003] Among them, multilayer ceramic capacitors are generally manufactured through the following steps.
[0004] First, after adding a plasticizer, a dispersant, etc. to a solution obtained by dissolving a binder resin such as a polyvinyl butyral resin or a poly (meth) acrylate resin in an organic solvent, a ceramic raw material powder is added, and the mixture is uniformly mixed by a mixing device such as a bead mill or a ball mill, and a slurry composition having a certain viscosity is obtained after degassing. The slurry composition is cast onto a support surface such as a polyethylene terephthalate film or a SUS plate after demolding using a scraper or a reverse roll coater, and the volatile components such as a solvent are distilled off by heating, and then the ceramic green sheet is obtained by peeling off from the support.
[0005] Next, a conductive paste to be the internal electrode is applied to the obtained ceramic green sheet by screen printing, and a plurality of sheets of the obtained material are alternately stacked and heat-pressed to produce a laminate. Then, a process of removing the binder resin component contained in the laminate by thermal decomposition, i.e., a so-called degreasing process, is performed, and the end surface of the ceramic sintered body obtained by firing is sintered to the external electrode to obtain a laminated ceramic capacitor.
[0006] However, conventional polyvinyl acetal resins produce a small amount of undissolved matter when dissolved in an organic solvent. If such undissolved matter exists, voids are likely to remain in the degreasing process and the firing process when manufacturing a laminated ceramic capacitor, or the dispersibility of the ceramic powder is reduced. As a result, the electrical properties of the obtained product are reduced.
[0007] Therefore, when the polyvinyl acetal resin is used for ceramic green sheets, it is necessary to mix it with an organic / inorganic compound or the like, dissolve it in an organic solvent, and then perform a filtration step to remove undissolved matter.
[0008] In this regard, Patent Document 1 proposes a polyvinyl acetal resin, wherein a polyvinyl acetal resin solution prepared by dissolving in a 1:1 mixed solvent of methyl ethyl ketone and / or toluene and ethanol to form a 5 wt% solution is filtered at a filtration temperature of 25°C and a filtration pressure of 10 mmHg using a filter having a mesh size of 5 μm, and the reduction rate of the filtration flow rate is less than 10%. In addition, Patent Document 2 discloses a polyvinyl acetal resin which absorbs the wave number 3100 to 3700 cm in the IR absorption spectrum. -1 The wave number of the peak in the range of A(cm -1 ) and the amount of hydroxyl groups (mol %) are controlled within a specific range. By using such a polyvinyl acetal resin, when dissolved in an organic solvent, less undissolved matter is left, and the filtration time can be shortened, thereby improving productivity.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2005-325342
[0012] Patent Document 2: International Publication No. 2021 / 060499 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, when the polyvinyl acetal resin described in Patent Document 1 is used, there is a problem that the tensile strength of the obtained ceramic green sheet is biased (non-uniform), and the stress at the breaking point becomes insufficient. In particular, as the ceramic green sheet becomes thinner, the uniformity of the tensile strength and the stress at the breaking point become important characteristics. In addition, when the polyvinyl acetal resin described in Patent Document 2 is used, the uniformity of the tensile strength of the obtained ceramic green sheet also has room for improvement.
[0015] An object of the present invention is to provide a polyvinyl acetal resin which, when used as a binder for a ceramic green sheet, can provide a ceramic green sheet having high uniformity of tensile strength and high stress at break.
[0016] Means for solving problems
[0017] The present invention (1) relates to a polyvinyl acetal resin, wherein the polyvinyl acetal resin is 13The ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the following formula (a) obtained by C-NMR (nuclear magnetic resonance) measurement to the total peak integral value of the methine C atom represented by (a)', (b)', and (c)' in the triple unit represented by the following formula (a), the following formula (b), and the following formula (c) is less than 0.23, the weight average molecular weight of the polyvinyl acetal resin is greater than 230,000, and in the high performance liquid chromatography (HPLC) measurement, the half-value width of the peak observed within the retention time range of 20 to 30 minutes is less than 0.50.
[0018] [Chemical formula 1]
[0019]
[0020] In the formula (b) and the formula (c), R is each independently hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0021] The present invention (2) relates to the polyvinyl acetal resin described in the present invention (1), wherein the solution viscosity is greater than 30 mPa·s and less than 600 mPa·s when a 5 mass % solution obtained by dissolving the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C.
[0022] The present invention (3) relates to the polyvinyl acetal resin according to the present invention (1) or (2), wherein the amount of hydroxyl groups is 23 mol% or more and 40 mol% or less.
[0023] The present invention (4) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (3), wherein the acetyl group content is 0.1 mol% or more and 5 mol% or less.
[0024] The present invention (5) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (4), wherein the molecular weight distribution of the polyvinyl acetal resin is 2.75 or less.
[0025] The present invention (6) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (5), which is used for a ceramic green sheet.
[0026] The present invention (7) relates to a slurry composition for ceramic green sheets, comprising the polyvinyl acetal resin according to any one of the present inventions (1) to (6), an organic solvent, and a ceramic powder.
[0027] The present invention (8) relates to a ceramic green sheet obtained by using the slurry composition for ceramic green sheets described in the present invention (7).
[0028] The present invention (9) relates to a multilayer ceramic capacitor obtained by using the ceramic green sheet described in the present invention (8).
[0029] Hereinafter, the present invention will be described in detail.
[0030] The present inventors have conducted intensive research and found that a ceramic green sheet obtained by using a polyvinyl acetal resin having uniform tensile strength and high stress at breaking point can be obtained. 13 The present invention was completed by the fact that the ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the above formula (a) obtained by C-NMR measurement to the total peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triple units represented by the above formulas (a), (b), and (c) (the ratio of the peak integral values of the triple unit formed by a three-sequence (Japanese: 3 chain) of structural units having a hydroxyl group), the half-value width of the peak derived from polyvinyl acetal in high performance liquid chromatography analysis, and the weight average molecular weight satisfy specific relationships.
[0031] Furthermore, when the polyvinyl acetal resin of the present invention is used as a slurry composition for ceramic green sheets, it is also possible to obtain an effect of preventing the viscosity of the slurry from increasing over time, thereby improving productivity.
[0032] For the polyvinyl acetal resin of the present invention, 13 The ratio of the peak integration value of the triplet unit composed of three sequences of structural units having a hydroxyl group obtained by C-NMR measurement is less than 0.23. By setting it in the above range, the uniformity of tensile strength and the time-dependent viscosity stability of the ceramic slurry can be improved.
[0033] The preferred lower limit of the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is 0.14, the preferred upper limit is 0.22, the further preferred lower limit is 0.15, and the further preferred upper limit is 0.21. That is, the peak integral value ratio of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is preferably 0.14 to 0.22, and more preferably 0.15 to 0.21.
[0034] When the ratio is less than 0.23, the solubility of the polyvinyl acetal resin and the dispersibility of the barium titanate are improved, and a more uniform ceramic green sheet can be produced, thereby improving the uniformity of the tensile strength.
[0035] It should be noted that in the present invention, the ratio of the peak integral value of "a triplet unit formed by three sequences of structural units having a hydroxyl group" is specified, thereby making it possible to more accurately confirm the continuity of the hydroxyl group compared to the case where the measurement is based on a binary unit formed by two sequences (Japanese: 2 chain).
[0036] The ratio of the peak integral values of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is the ratio of the sum of the peak integral values of the methine C atoms represented by (a)' in the triplet unit represented by the above formula (a) to the sum of the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triplet units represented by the above formula (a), the above formula (b), and the above formula (c). 13 The measurement was performed by C-NMR.
[0037] The sum of the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triplet units represented by the above formula (a), the above formula (b), and the above formula (c) [I(a)'+I(b)'+I(c)'], when the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' are calculated by 13 C-NMR (nuclear magnetic resonance) measurement 13 When the integrated value of the peak attributed to the methine C atom at the position (f)' of the triple unit represented by the following formula (f) in the C-NMR spectrum is set as I(f)', the integrated value of the peak attributed to the methine C atom at the position (g)' of the triple unit represented by the following formula (g) is set as I(g)', the integrated value of the peak attributed to the methine C atom at the position (k)'2 of the triple unit represented by the following formula (k) is set as I(k)'2, the integrated value of the peak attributed to the methine C atom at the position (i)' of the triple unit represented by the following formula (i) is set as I(i)', the integrated value of the peak attributed to the methine C atom at the position (j)' of the triple unit represented by the following formula (j) is set as I(j)', and the integrated value of the peak attributed to the methine C atom at the position (m)' of the triple unit represented by the following formula (m) is set as I(m)', it can be calculated by the sum of these, that is, the following formula (4).
[0038] I(a)'+I(b)'+I(c)'=I(f)'+I(g)'+I(k)'2+I(i)'+I(j)'+I(m)' (4)
[0039] [Chemical formula 2]
[0040]
[0041] R in formula (i), formula (j) and formula (m) 6 ~R 9Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0042] Regarding the peak integral value [I(a)'] of the methine C atom represented by (a)' in the triple unit represented by the above formula (a), 13 C-NMR (nuclear magnetic resonance) measurement 13 When the integral value of the peak attributable to the secondary methyl C atom at the position (f)' of the triple unit represented by the above formula (f) in the C-NMR spectrum is set as I(f)', the integral value of the peak attributable to the secondary methyl C atom at the position (g)' of the triple unit represented by the above formula (g) is set as I(g)', and the integral value of the peak attributable to the secondary methyl C atom at the position (k)'2 of the triple unit represented by the above formula (k) is set as I(k)'2, it can be calculated by their sum, that is, the following formula (5).
[0043] I(a)'=I(f)'+I(g)'+I(k)'2 (5)
[0044] The ratio of the peak integral value of the triplet unit represented by the above formula (a) to the sum of the peak integral values of the triplet units represented by the above formula (a), the above formula (b) and the above formula (c) [I(a)' / (I(a)'+I(b)'+I(c)')] can be calculated by the following formula (6).
[0045] I(a)' / (I(a)'+I(b)'+I(c)')=(I(f)'+I(g)'+I(k)'2) / (I(f)'+I(g)'+I(k)'2+I(i)'+I(j)'+I(m)')(6)
[0046] exist 13 In the C-NMR spectrum, the above I(f)' is an integrated value of a peak in the range of 64.0 to 64.8 ppm, and the above I(g)' is an integrated value of a peak in the range of 65.8 to 66.7 ppm.
[0047] In addition, I(i)' is the peak integrated value in the range of 61.5 to 63.1 ppm, I(j)' is the peak integrated value in the range of 64.8 to 65.8 ppm, and I(m)' is the peak integrated value in the range of 63.1 to 64.0 ppm.
[0048] The above I(k)'2 is an integral value of the peak in the range of 66.7 to 70.5 ppm, but since it partially overlaps with the peaks of other structures, it can be calculated by the difference with other peaks. For example, since the peak attributed to the methine C atom at the position (e1)' of the following structural unit (e) also exists in the range of 66.7 to 70.5 ppm, the peak integral value can be calculated using the following formula (7).
[0049] Here, I(t) is the peak integral value in the range of 66.7 to 70.5 ppm, I(d1)' is the peak integral value in the range of 98.5 to 101.5 ppm to which the methine C atom of the acetal part having a meso-type 6-membered acetal ring at the position (d1)' of the structural unit (d) belongs, and I(e1)' is the peak integral value in the range of 91.5 to 101.5 ppm to which the methine C atom of the acetal part having a racemic 6-membered acetal ring at the position (e1)' of the structural unit (e) belongs. I(d2)' is the peak integration value in the range of 71.0 to 74.6 ppm to which the secondary methyl C atom of the main chain having a racemic 6-membered acetal ring at the position (d2)' of the structural unit (d) is attributed, and I(e2)' is the peak integration value in the range of 66.7 to 70.5 ppm to which the secondary methyl C atom of the main chain having a racemic 6-membered acetal ring at the position (e2)' of the structural unit (e) is attributed.
[0050] I(k) '2=I(t) -I(d1) '×I(e2) '÷I(d2) ' (7)
[0051] [Chemical formula 3]
[0052]
[0053] R in formula (d) and formula (e) 4 , R 5 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0054] The ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups can be adjusted, for example, by appropriately setting the saponification degree of the raw material polyvinyl alcohol resin, the type of aldehyde, the conditions of the acetalization reaction, the acetal group amount, the hydroxyl group amount, the acetyl group amount, the weight average molecular weight, the number average molecular weight, the molecular weight distribution, etc. of the polyvinyl alcohol acetal resin.
[0055] The polyvinyl acetal resin of the present invention preferably has a solution viscosity of 30 mPa·s to 600 mPa·s when a 5 mass % solution of the polyvinyl acetal resin dissolved in a 1:1 mixed solvent of ethanol and toluene is measured using a Brookfield viscometer at a solution temperature of 20°C.
[0056] From the viewpoint of being able to improve the tensile strength of the ceramic green sheet and the time-dependent viscosity stability of the ceramic green sheet slurry, the above viscosity is 30 mPa·s or more, more preferably 50 mPa·s or more, and particularly preferably 60 mPa·s or more. From the viewpoint of being able to improve the viscosity stability of the ceramic slurry composition, the above viscosity is 600 mPa·s or less, more preferably 400 mPa·s or less, and particularly preferably 200 mPa·s or less. That is, the above viscosity is preferably 30 to 600 mPa·s, more preferably 50 to 400 mPa·s, and particularly preferably 60 to 200 mPa·s.
[0057] As the B-type viscometer, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. can be used. In addition, the rotor and rotation speed when measuring the viscosity are preferably appropriately adjusted according to the solution viscosity, and for example, it is preferred to use SPINDLE No. M1 to M4 for measurement within a rotation speed range of 0.3 to 100 rpm.
[0058] The above viscosity can be adjusted by appropriately setting the saponification degree of the raw material polyvinyl alcohol resin, the average degree of polymerization, the conditions of the acetalization reaction, the acetal group content, the hydroxyl group content, the acetyl group content, the weight average molecular weight, the number average molecular weight, the molecular weight distribution, etc. of the polyvinyl acetal resin.
[0059] The polyvinyl acetal resin of the present invention preferably has a structural unit having an acetal group represented by the following formula (1), a structural unit having a hydroxyl group represented by the following formula (2), and a structural unit having an acetyl group represented by the following formula (3).
[0060] [Chemical formula 4]
[0061]
[0062] In the above formula (1), R 1 It represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0063] In the above formula (1), R 1 In the case of an alkyl group having 1 to 20 carbon atoms, examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, 2-ethylhexyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, and octadecyl. Among them, methyl and n-propyl are preferred.
[0064] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetal group represented by the above formula (1) (hereinafter also referred to as "acetal group amount") preferably has a lower limit of 55 mol% and an upper limit of 75 mol%.
[0065] When the acetal group content is 55 mol% or more, the solubility in an organic solvent can be improved, and when the acetal group content is 75 mol% or less, a polyvinyl acetal resin having excellent tensile strength can be obtained.
[0066] The more preferred lower limit of the acetal group content is 57 mol%, the further preferred lower limit is 60 mol%, and the more preferred upper limit is 73 mol%. That is, the acetal group content is preferably 55 to 75 mol%, more preferably 57 to 73 mol%, and further preferably 60 to 73 mol%.
[0067] The above acetal group amount can be 1 The measurement was performed by H-NMR.
[0068] In addition, regarding the method for calculating the amount of acetal groups, since the acetal groups of the polyvinyl acetal resin are obtained by acetalizing two hydroxyl groups of polyvinyl alcohol, a method of counting the two hydroxyl groups acetalized was adopted.
[0069] In the polyvinyl acetal resin of the present invention, the content of the structural unit having a hydroxyl group represented by the general formula (2) (hereinafter also referred to as "hydroxyl amount") preferably has a lower limit of 23 mol% and an upper limit of 40 mol%.
[0070] When the hydroxyl group content is 23 mol% or more, a polyvinyl acetal resin having high toughness can be obtained, and when the hydroxyl group content is 40 mol% or less, the solubility in an organic solvent can be sufficiently improved.
[0071] The more preferred lower limit of the amount of hydroxyl groups is 25 mol%, the further preferred lower limit is 27 mol%, the particularly preferred lower limit is 29 mol%, the more preferred upper limit is 35 mol%, and the further preferred upper limit is 33 mol%. That is, the amount of hydroxyl groups is preferably 23 to 40 mol%, more preferably 25 to 35 mol%, further preferably 27 to 33 mol%, and particularly preferably 29 to 33 mol%.
[0072] The above hydroxyl amount can be 1 The measurement was performed by H-NMR.
[0073] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetyl group represented by the general formula (3) (hereinafter also referred to as "acetyl group amount") preferably has a lower limit of 0.1 mol % and an upper limit of 5 mol %.
[0074] If the acetyl group content is 0.1 mol% or more, the viscosity of the ceramic green sheet slurry composition can be suppressed due to hydrogen bonding within and between molecules of the hydroxyl groups in the polyvinyl acetal resin. If the acetyl group content is 5 mol% or less, the flexibility of the polyvinyl acetal resin will not be excessively increased, and the handling property can be improved.
[0075] The more preferred lower limit of the acetyl group amount is 0.3 mol%, the further preferred lower limit is 0.5 mol%, the more preferred upper limit is 4 mol%, the further preferred upper limit is 3 mol%, and the particularly preferred upper limit is 2 mol%. That is, the acetyl group amount is preferably 0.1 to 5 mol%, more preferably 0.3 to 4 mol%, further preferably 0.5 to 3 mol%, and particularly preferably 0.5 to 2 mol%.
[0076] The above acetyl group amount can be 1 The measurement was performed by H-NMR.
[0077] The lower limit of the weight average molecular weight (Mw) of the polyvinyl acetal resin of the present invention is 230000. When the weight average molecular weight is 230000 or more, the tensile strength can be made good.
[0078] The lower limit of the weight average molecular weight is preferably 270,000, more preferably 290,000, and still more preferably 330,000.
[0079] From the viewpoint of improving the temporal viscosity stability of the ceramic green sheet slurry, the upper limit is preferably 700000, and more preferably 450000. That is, the weight average molecular weight is preferably 270000 to 700000, more preferably 290000 to 450000, and even more preferably 330000 to 450000.
[0080] The number average molecular weight (Mn) of the polyvinyl acetal resin of the present invention preferably has a lower limit of 98,000, an upper limit of 250,000, and a more preferred upper limit of 160,000. That is, the number average molecular weight is preferably 98,000 to 250,000, and more preferably 98,000 to 160,000.
[0081] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the polyvinyl acetal resin of the present invention, i.e., the molecular weight distribution, preferably has a lower limit of 2.2, a more preferred lower limit of 2.4, a preferred upper limit of 3.5, more preferably 3.0, further preferably 2.75, a particularly preferred upper limit of 2.73, and a most preferred upper limit of 2.7. That is, the above-mentioned Mw / Mn is preferably 2.2 to 3.5, more preferably 2.4 to 3.0, further preferably 2.4 to 2.75, particularly preferably 2.4 to 2.73, and most preferably 2.4 to 2.7. By setting it in the above range, the time-dependent viscosity stability of the slurry for ceramic green sheets and the uniformity of the tensile strength of the ceramic green sheets can be improved.
[0082] The Mw and Mn can be measured, for example, by gel permeation chromatography (GPC) using an appropriate standard (for example, a polystyrene standard). Examples of the column used when measuring the Mw and Mn include TSKgel SuperHZM-H and the like.
[0083] For the polyvinyl acetal resin of the present invention, when a thin film ceramic green sheet is produced, from the viewpoint of maintaining mechanical strength, the lower limit of the average degree of polymerization is preferably 600, more preferably 800, and further preferably 1000. From the viewpoint of solubility in organic solvents and dissolution viscosity, the upper limit is preferably 4000, more preferably 3000, and further preferably 2500. That is, the average degree of polymerization is preferably 600 to 4000, more preferably 800 to 3000, and further preferably 1000 to 2500.
[0084] It should be noted that the average degree of polymerization of the polyvinyl acetal resin is the same as the average degree of polymerization of the raw material polyvinyl alcohol. The average degree of polymerization can be measured in accordance with JIS K6726.
[0085] The polyvinyl acetal resin of the present invention has a half-value width (HPLC half-value width) of a peak observed in a retention time range of 20 to 30 minutes in high performance liquid chromatography (HPLC) measurement of 0.50 or less. By making the HPLC half-value width within the above range, the uniformity of the tensile strength of the obtained ceramic green sheet can be improved.
[0086] The HPLC half-value width is preferably 0.30 to 0.50, more preferably 0.31 to 0.45, further preferably 0.32 to 0.42, and particularly preferably 0.33 to 0.40. That is, the HPLC half-value width is preferably 0.30 to 0.50, more preferably 0.31 to 0.45, further preferably 0.32 to 0.42, and particularly preferably 0.33 to 0.40.
[0087] It should be noted that the above-mentioned half-value width refers to the peak width at the height position of 1 / 2 (50%) of the observed peak.
[0088] In addition, the above-mentioned HPLC determination refers to a reverse-phase partition gradient high-performance liquid chromatography determination using an eluent of a mixed solution of water-tetrahydrofuran / isopropanol = 7 / 3 [volume ratio].
[0089] The above-mentioned HPLC determination can be carried out, for example, under the following determination conditions.
[0090] HPLC device: Prominence manufactured by Shimadzu Corporation
[0091] Sample concentration: 0.2 mg / mL
[0092] Sample solvent: Tetrahydrofuran (THF) / Isopropanol (IPA) = 7 / 3 [volume ratio]
[0093] Injection volume: 20 μL
[0094] Detector: Evaporative light scattering detector (hereinafter referred to as ELSD) "ELSD_LTII" manufactured by Shimadzu Corporation
[0095] Nebulizer gas: Nitrogen (gas supply pressure = 350 kPa)
[0096] Detector temperature: 35 °C
[0097] ODS column: "XBridge BEH C18 (inner diameter 2.1 μm × 10 cm, packing particle size 3.5 μm)" manufactured by Waters Corporation
[0098] Column temperature: 45 °C
[0099] Liquid delivery flow rate: Flow rate (Japanese: 惣流量) 0.4 mL / minute
[0100] The HPLC determination of the polyvinyl acetal resin of the present invention can be carried out, for example, according to the following steps.
[0101] Solvents of different polarities are used as the mobile phase. It is preferable to use water as the high-polarity mobile phase A and THF / IPA = 7 / 3 [volume ratio] as the low-polarity mobile phase B. At the moment before sample injection, the inside of the column of the HPLC system is filled with a mixed solvent of mobile phase A / mobile phase B at a volume ratio of 9 / 1. The sample is injected in this state, and starting from immediately after the sample injection, the proportion of mobile phase B in the mobile phase is increased at a constant speed (4.5 vol% / minute) for 20 minutes. Only mobile phase B is flowed for 10 minutes starting from 20 minutes after injection.
[0102] The polyvinyl acetal resin has low polarity sites derived from acetal ring monomers and vinyl ester monomers and high polarity sites derived from vinyl alcohol monomers in the molecule. Therefore, it is found that the distribution of low polarity sites and high polarity sites in the molecule of the polyvinyl acetal resin affects the uniformity of tensile strength. The peak half-value width W obtained by HPLC analysis is 0.5h It is possible to determine the distribution of low polarity sites and high polarity sites in the polymer. 0.5h If W increases, it means that the distribution of low polarity and high polarity sites becomes wider. 0.5h A decrease in polarity indicates that the distribution has become narrower. By narrowing the distribution of polarity, the polyvinyl acetal resin is uniformly dissolved, and a uniform ceramic green sheet can be produced, thereby improving the uniformity of tensile strength.
[0103] The HPLC half-value width (peak half-value width W) obtained by the above HPLC measurement 0.5h ) For example, it can be adjusted by appropriately setting the saponification degree of the raw material polyvinyl alcohol resin, the saponification degree distribution, the conditions of the acetalization reaction, the acetal group amount, hydroxyl group amount, acetyl group amount, weight average molecular weight, number average molecular weight, molecular weight distribution, etc. of the polyvinyl alcohol acetal resin.
[0104] The polyvinyl acetal resin of the present invention can be generally produced by acetalizing a polyvinyl alcohol resin.
[0105] As the polyvinyl alcohol resin, for example, a conventionally known polyvinyl alcohol resin such as a resin produced by saponifying a polyvinyl acetate-based resin with an alkali, an acid, ammonia water, or the like can be used.
[0106] The polyvinyl alcohol resin may be completely saponified, but if at least one unit having a dihydroxyl group (Japanese: 2-linked hydrocarbyl group) at the meso position and the racemic position is present at least in one part of the main chain, it does not need to be completely saponified and may be a partially saponified polyvinyl alcohol resin. In addition, as the polyvinyl alcohol resin, a copolymer of a monomer copolymerizable with vinyl alcohol such as an ethylene-vinyl alcohol copolymer resin and a partially saponified ethylene-vinyl alcohol copolymer resin and vinyl alcohol may also be used.
[0107] Examples of the polyvinyl acetate-based resin include ethylene-vinyl acetate copolymers and the like.
[0108] The saponification degree of the polyvinyl alcohol resin is preferably 70 mol% to 99.5 mol%, more preferably 95 mol% to 99.3 mol%. That is, the saponification degree is preferably 70 to 99.5 mol%, more preferably 95 to 99.3 mol%.
[0109] By using the polyvinyl alcohol resin, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin, the viscosity, and the HPLC half-value width can be set within predetermined ranges.
[0110] The acetalization is preferably carried out in an aqueous solvent, in a mixed solvent of water and an organic solvent compatible with water, or in an organic solvent.
[0111] As the organic solvent compatible with water, for example, an alcohol organic solvent can be used.
[0112] Examples of the organic solvent include alcohol organic solvents, aromatic organic solvents, aliphatic ester solvents, ketone solvents, lower alkane solvents, ether solvents, amide solvents, and amine solvents.
[0113] Examples of the alcohol-based organic solvent include methanol, ethanol, n-propanol, isopropanol, n-butanol, and tert-butanol.
[0114] Examples of the aromatic organic solvent include xylene, toluene, ethylbenzene, and methyl benzoate.
[0115] Examples of the aliphatic ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, methyl acetoacetate, and ethyl acetoacetate.
[0116] Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, benzophenone, and acetophenone.
[0117] Examples of the lower alkane solvent include hexane, pentane, octane, cyclohexane, and decane.
[0118] Examples of the ether solvent include diethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol diethyl ether.
[0119] Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetanilide.
[0120] Examples of the amine solvent include ammonia, trimethylamine, triethylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, and pyridine.
[0121] These solvents may be used as a single component (Japanese: monomer) or as a mixture of two or more thereof. Among these solvents, ethanol, n-propanol, isopropanol, and tetrahydrofuran are particularly preferred from the viewpoint of solubility in the resin and ease of purification.
[0122] The above-mentioned acetalization is preferably carried out in the presence of an acid catalyst.
[0123] The acid catalyst is not particularly limited, and examples thereof include mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, carboxylic acids such as formic acid, acetic acid, and propionic acid, and sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid. These acid catalysts may be used alone or in combination of two or more compounds. Among them, hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is particularly preferred.
[0124] As the aldehyde used in the acetalization, there can be mentioned aldehydes having a chain aliphatic group, a cyclic aliphatic group or an aromatic group having 1 to 10 carbon atoms. As these aldehydes, conventionally known aldehydes can be used. The aldehyde used in the acetalization reaction is not particularly limited, and examples thereof include aliphatic aldehydes, aromatic aldehydes, and the like.
[0125] Examples of the aliphatic aldehydes include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, n-hexanal, 2-ethylbutyraldehyde, 2-ethylhexanal, n-heptylaldehyde, n-octanal, n-nonylaldehyde, n-decanal, and valeraldehyde.
[0126] Examples of the aromatic aldehyde include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde.
[0127] These aldehydes may be used alone or in combination of two or more. As aldehydes, formaldehyde, acetaldehyde, butyraldehyde, 2-ethylhexanal, and n-nonanal are preferred, which have excellent acetalization reactivity, can provide sufficient internal plasticization effect to the generated resin, and can give good flexibility as a result. In addition, formaldehyde, acetaldehyde, and butyraldehyde are more preferred from the perspective of obtaining an adhesive composition having particularly excellent impact resistance and adhesion to metals.
[0128] The amount of the aldehyde added can be appropriately set according to the acetal group amount of the target polyvinyl acetal resin. In particular, if it is preferably 55 mol% or more and 95 mol% or less, and more preferably 60 mol% or more and 90 mol% or less relative to 100 mol% of polyvinyl alcohol, the acetalization reaction is efficiently carried out and the unreacted aldehyde is easily removed, so it is preferred. That is, the amount of the aldehyde added is preferably 55 to 95 mol%, and more preferably 60 to 90 mol%.
[0129] The temperature when the aldehyde is added (aldehyde charging temperature) is preferably 0° C. or higher, more preferably 10° C. or higher, further preferably 15° C. or higher, particularly preferably 18° C. or higher, and preferably 55° C. or lower, more preferably 50° C. or lower, further preferably 45° C. or lower, and particularly preferably 40° C. or lower. That is, the aldehyde charging temperature is preferably 0 to 55° C., more preferably 10 to 50° C., further preferably 15 to 45° C., and particularly preferably 18 to 40° C.
[0130] By setting the aldehyde charging temperature as described above, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin, the viscosity, and the HPLC half-value width can be within predetermined ranges.
[0131] During the acetalization reaction, it is preferred to perform a hydrolysis process using hydrochloric acid or a saponification process using sodium hydroxide before the acetalization reaction, wherein the hydrolysis process using hydrochloric acid is preferably performed. By performing the hydrolysis process using hydrochloric acid, the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups in the polyvinyl alcohol acetal resin, the viscosity, and the HPLC half-value width can be within a specified range. For example, the hydrolysis process using hydrochloric acid refers to a process in which polyvinyl alcohol is heated and dissolved in water, hydrochloric acid is added, and heated and stirred for a certain period of time to hydrolyze the acetyl groups contained in the polyvinyl alcohol into hydroxyl groups. The hydrolysis temperature, hydrolysis time, and amount of hydrochloric acid can be appropriately adjusted according to the saponification degree of the raw material polyvinyl alcohol and the target saponification degree after hydrolysis.
[0132] The hydrolysis temperature is preferably 50° C. or higher, and preferably 90° C. or lower. It is more preferably 53° C. or higher and 85° C. or lower, further preferably 55° C. or higher and 80° C. or lower, and particularly preferably 60° C. or higher and 75° C. or lower. That is, the hydrolysis temperature is preferably 50 to 90° C., more preferably 53 to 85° C., further preferably 55 to 80° C., and particularly preferably 60 to 75° C.
[0133] The hydrolysis time is preferably 30 minutes or more, preferably 10 hours or less. It is more preferably 45 minutes or more and 8 hours or less, further preferably 1 hour or more and 7 hours or less, and particularly preferably 2 hours or more and 6 hours or less. That is, the hydrolysis time is preferably 30 minutes to 10 hours, more preferably 45 minutes to 8 hours, further preferably 1 to 7 hours, and particularly preferably 2 to 6 hours.
[0134] The amount of hydrochloric acid is preferably 10 parts by weight or more, preferably 250 parts by weight or less, based on 100 parts by weight of polyvinyl alcohol. It is more preferably 15 parts by weight or more and 200 parts by weight or less, and further preferably 30 parts by weight or more and 120 parts by weight or less. That is, the amount of hydrochloric acid is preferably 10 to 250 parts by weight, more preferably 15 to 200 parts by weight, and further preferably 30 to 120 parts by weight, based on 100 parts by weight of polyvinyl alcohol.
[0135] In the acetalization reaction, it is preferred that the aldehyde is introduced at a predetermined temperature and then maintained at the predetermined temperature for a predetermined period of time.
[0136] The retention time (reaction temperature) in the acetalization reaction is preferably 0.1 hours to 7 hours, more preferably 0.5 hours to 5 hours. That is, the retention time is preferably 0.1 to 7 hours, more preferably 0.5 to 5 hours. By setting the retention time as the above, the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups in the polyvinyl acetal resin, the viscosity, and the HPLC half-value width can be within the specified range.
[0137] The holding temperature in the acetalization reaction is preferably -5°C to 50°C, more preferably 5°C to 40°C. That is, the holding temperature is preferably -5 to 50°C, more preferably 5 to 40°C. By setting the holding temperature to the above, the ratio of the peak integrated value of the triplet unit formed by the three sequences of the structural units having a hydroxyl group in the polyvinyl acetal resin, the viscosity, and the HPLC half-value width can be within a predetermined range.
[0138] The temperature difference between the hydrolysis temperature and the holding temperature (hydrolysis temperature - holding temperature) is preferably 5°C to 50°C, more preferably 10°C to 40°C.
[0139] The acetalization reaction can be carried out by adding aldehyde at a predetermined temperature, raising the temperature at a predetermined rate, and then maintaining the temperature for a predetermined period of time.
[0140] The heating time in the acetalization reaction is preferably 30 minutes to 500 minutes, more preferably 60 minutes to 400 minutes, and even more preferably 120 minutes to 300 minutes. That is, the heating time is preferably 30 to 500 minutes, more preferably 60 to 400 minutes, and even more preferably 120 to 300 minutes.
[0141] In addition, the temperature increase rate is preferably 0.1° C. / minute or more and 2° C. / minute or less. In other words, the temperature increase rate is preferably 0.1 to 2° C. / minute.
[0142] By heating at the above heating time and heating rate, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin, the viscosity, and the HPLC half-value width can be within predetermined ranges.
[0143] A slurry composition for ceramic green sheets can be prepared by mixing an organic solvent and a ceramic powder with the polyvinyl acetal resin of the present invention.
[0144] The organic solvent is not particularly limited, and for example, any solvent that can dissolve the polyvinyl acetal resin is not particularly limited, and examples thereof include ketones such as acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. In addition, alcohols such as methanol, ethanol, isopropyl alcohol, and butanol, and aromatic hydrocarbons such as toluene and xylene can be mentioned. In addition, esters such as methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, butyl butyrate, methyl valerate, ethyl valerate, butyl valerate, methyl caproate, ethyl caproate, butyl caproate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate can be mentioned. In addition, methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate can be mentioned. In particular, alcohols, ketones, aromatic hydrocarbons, and mixed solvents thereof are particularly preferred from the viewpoint of coating properties and drying properties, and mixed solvents of ethanol and toluene and mixed solvents of methyl ethyl ketone and toluene are more preferred.
[0145] The content of the organic solvent in the slurry composition for ceramic green sheets is set according to the type of polyvinyl acetal resin used, etc., and is not particularly limited. If it is too little, it is difficult to exert the solubility required for mixing. In addition, if it is too much, the viscosity of the slurry composition for ceramic green sheets sometimes becomes too low, and the handling property when making ceramic green sheets deteriorates. Therefore, the content of the organic solvent is preferably 20% by weight or more and 80% by weight or less. That is, the content of the organic solvent is preferably 20 to 80% by weight.
[0146] As the above-mentioned ceramic powder, the metal or non-metal oxide or non-oxide powder used in the manufacture of ceramics can be cited. In addition, the composition of these powders can be a single composition, and the powder in the compound state can also be used alone or in combination. It should be noted that the constituent elements of the metal oxide or non-oxide, including cations or anions, can all be formed by a single element, can also be formed by multiple elements, and can also include additives added to improve the characteristics of the oxide or non-oxide. Specifically, oxides, carbides, nitrides, borides, sulfides, etc. of Li, K, Mg, B, Al, Si, Cu, Ca, Sr, Ba, Zn, Cd, Ga, In, Y, lanthanides, actinides, Ti, Zr, Hf, Bi, V, Nb, Ta, W, Mn, Fe, Co, Ni, etc. can be cited.
[0147] In addition, if the specific substances of oxide powders containing multiple metal elements, which are generally called composite oxides, are classified according to the crystal structure, substances having a perovskite structure include: NaNbO3, SrZrO3, PbZrO3, SrTiO3, BaZrO3, PbTiO3, BaTiO3, etc. As substances having a spinel structure, MgAl2O4, ZnAl2O4, CoAl2O4, NiAl2O4, MgFe2O4, etc. As substances having an ilmenite structure, MgTiO3, MnTiO3, FeTiO3, etc. are mentioned. As substances having a garnet structure, GdGa5O4, ZnAl2O4, CoAl2O4, NiAl2O4, MgFe2O4, etc. are mentioned. 12 、Y6Fe5O 12 Etc. Among them, the modified polyvinyl acetal resin of the present invention exhibits high characteristics in a ceramic green sheet obtained by mixing with BaTiO3 powder.
[0148] The slurry composition for ceramic green sheets may contain a plasticizer. By adding a plasticizer, the mechanical strength and flexibility of the obtained ceramic green sheets can be greatly improved.
[0149] Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and alkylene glycol diesters such as triethylene glycol-di-heptanoate.
[0150] The average particle size of the ceramic powder is not particularly limited, but is preferably 0.5 μm or less for, for example, production of a thin-layer ceramic green sheet (thickness 5 μm or less).
[0151] In the slurry composition for ceramic green sheets, the preferred lower limit of the content of the plasticizer is 7 parts by weight, and the more preferred lower limit is 8.5 parts by weight, and the preferred upper limit is 40 parts by weight, and the more preferred upper limit is 30 parts by weight, relative to 100 parts by weight of the polyvinyl acetal resin. That is, the content of the plasticizer is preferably 7 to 40 parts by weight, and more preferably 8.5 to 30 parts by weight.
[0152] The ceramic green sheet slurry composition may contain other resins such as polyvinyl acetal resin, acrylic resin, ethyl cellulose, etc. other than the polyvinyl acetal resin of the present invention within a range that does not impair the effects of the present invention. In such a case, the content of the polyvinyl acetal resin of the present invention is preferably 50% by weight or more relative to the total binder resin.
[0153] The slurry composition for ceramic green sheets may contain dispersants, antioxidants, ultraviolet absorbers, surfactants, fillers, release agents, etc. as needed. Other resins such as acrylic resins and urethane resins may also be added in small amounts as needed.
[0154] The method for producing the slurry composition for ceramic green sheets is not particularly limited, and examples thereof include a method of mixing the polyvinyl acetal resin of the present invention, an organic solvent, ceramic powder, and various additives added as needed using various mixers such as a ball mill, a mixing mill, and a three-roll mill.
[0155] After the slurry composition for ceramic green sheets is applied, it is dried by heating to obtain ceramic green sheets.
[0156] The ceramic green sheets can be used to manufacture ceramic electronic components. For example, the ceramic electronic components can be manufactured by applying an electrode layer paste on the surface of the ceramic green sheets, and degreasing and firing the laminated body obtained by stacking and heat-pressing the ceramic green sheets with the electrode layers formed thereon.
[0157] The method for applying the slurry composition for ceramic green sheets is not particularly limited, and examples thereof include methods using a roll coater, a die coater, a curtain coater, etc. As other specific methods, conventionally known methods can be used.
[0158] The ceramic electronic components are not particularly limited, and examples thereof include laminated ceramic capacitors, laminated ceramic inductors, capacitors, piezoelectric actuators, laminated varistors, laminated thermistors, EMI filters, aluminum nitride multilayer substrates, aluminum oxide multilayer substrates, etc. Such laminated ceramic capacitors are also one of the present invention.
[0159] In the method for producing the ceramic electronic component, a step of applying an electrode layer paste on the surface of the ceramic green sheet is performed.
[0160] As the electrode layer paste, for example, polyvinyl acetal resin, ethyl cellulose, acrylic resin, etc. can be dissolved in an organic solvent as a binder resin, and a conductive powder can be dispersed. These resins can be used alone or in combination of two or more. The electrode layer paste containing polyvinyl acetal resin shows excellent adhesion to the ceramic green sheet in the heating and pressing process, so it is preferred.
[0161] In the manufacturing method of the above-mentioned ceramic electronic component, after the above-mentioned ceramic green sheets with electrode layers are produced, the ceramic green sheets with electrode layers produced in the same manner are stacked and heated and pressed to obtain a stacked body, which is then degreased and fired, thereby obtaining a stacked ceramic electronic component that solves problems such as sheet erosion (Japanese: シートアタック) and cracks.
[0162] It should be noted that the heat compression bonding step and the step of degreasing and firing the laminated body are not particularly limited, and conventionally known methods can be used.
[0163] Effects of the Invention
[0164] According to the present invention, it is possible to provide a polyvinyl acetal resin which, when used as a binder for a ceramic green sheet, can provide a ceramic green sheet having uniform tensile strength and high stress at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0165] Figure 1 The polyvinyl acetal resin obtained in Example 11 was 13 C-NMR measurement, measurement data when measuring the ratio of the peak integrated value of a triplet unit consisting of three sequences of structural units having a hydroxyl group.
[0166] Figure 2 These are the measurement data obtained by subjecting the polyvinyl acetal resin obtained in Example 5 to HPLC measurement. DETAILED DESCRIPTION
[0167] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0168] (Example 1)
[0169] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40°C, 160 g of n-butylaldehyde was added, and the mixture was kept at 40°C for 3 hours to perform acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0170] (Example 2)
[0171] 3000 g of pure water was added to 200 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40°C, 107 g of n-butylaldehyde was added, and the mixture was kept at 40°C for 3 hours to perform acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0172] (Example 3)
[0173] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1500, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40°C, 160 g of normal butyraldehyde was added thereto, and the mixture was kept at 40°C for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0174] (Example 4)
[0175] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 5 hours. The mixture was cooled to 40°C, 160 g of n-butylaldehyde was added, and the mixture was kept at 40°C for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0176] (Example 5)
[0177] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 60°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 5 hours. The mixture was cooled to 40°C, 160 g of n-butylaldehyde was added, and the mixture was kept at 40°C for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0178] (Example 6)
[0179] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 80° C., 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 1 hour. The mixture was cooled to 40° C., 160 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0180] (Example 7)
[0181] 3000 g of pure water was added to 150 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%, first PVA) and 150 g of polyvinyl alcohol resin (average degree of polymerization 1500, degree of saponification 88.1 mol%, second PVA), and stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and kept for 3 hours. After cooling to 40°C, 160 g of n-butyraldehyde was added, and the acetalization reaction was carried out at 40°C for 3 hours, the reaction was terminated, neutralized, washed with water and dried by conventional methods, and a white powder of polyvinyl alcohol acetal resin was obtained.
[0182] (Example 8)
[0183] 3000 g of pure water was added to 150 g of polyvinyl alcohol resin (average degree of polymerization 2400, saponification degree 88.1 mol%, first PVA) and 150 g of polyvinyl alcohol resin (average degree of polymerization 1500, saponification degree 88.1 mol%, second PVA), and stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, 200 g of hydrochloric acid with a concentration of 35% by weight was added, and kept for 3 hours. After cooling to 40°C, 160 g of n-butyraldehyde was added, and the acetalization reaction was carried out at 40°C for 3 hours, the reaction was terminated, neutralized, washed with water and dried by conventional methods, and a white powder of polyvinyl alcohol acetal resin was obtained.
[0184] (Example 9)
[0185] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0186] (Example 10)
[0187] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 250 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0188] (Example 11)
[0189] 3000 g of pure water was added to 200 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 70°C, 100 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 10 hours. The mixture was cooled to 40°C, 110 g of n-butylaldehyde was added, and the mixture was kept at 40°C for 5 hours to carry out acetalization reaction, and the reaction was terminated. The mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0190] (Example 12)
[0191] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90°C for about 2 hours. The solution was cooled to 70°C, 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 10°C, and 165 g of normal butyraldehyde was added. Next, the mixture was heated to 40°C over 60 minutes, and the acetalization reaction was carried out at 40°C for 3 hours. The reaction was terminated, and the mixture was neutralized, washed with water, and dried by conventional methods to obtain a white powder of polyvinyl alcohol acetal resin.
[0192] (Example 13)
[0193] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90°C for about 2 hours. The solution was cooled to 70°C, 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 10°C, and 165 g of normal butyraldehyde was added. Next, the mixture was heated to 40°C over 180 minutes, and the acetalization reaction was carried out at 40°C for 3 hours, after which the reaction was terminated, and the mixture was neutralized, washed with water, and dried by conventional methods to obtain a white powder of polyvinyl alcohol acetal resin.
[0194] (Example 14)
[0195] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 20° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 20° C. for 7 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0196] (Example 15)
[0197] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1000, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0198] (Example 16)
[0199] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 2500, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0200] (Example 17)
[0201] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 70° C., 215 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 40° C., 165 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0202] (Comparative Example 1)
[0203] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 98.0 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butylaldehyde were added thereto, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0204] (Comparative Example 2)
[0205] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 3000, degree of saponification 98.5 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butylaldehyde were added thereto, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0206] (Comparative Example 3)
[0207] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 800, degree of saponification 98.4 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 150 g of n-butylaldehyde were added thereto, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0208] (Comparative Example 4)
[0209] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 20° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto, and the temperature was increased at a temperature increase rate of 0.30° C. / min (temperature increase time 150 minutes). After the acetalization reaction was carried out at 65° C. for 2 hours, the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0210] (Comparative Example 5)
[0211] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., and 200 g of hydrochloric acid with a concentration of 35% by weight was added and kept for 2 hours. Next, 145 g of n-butylaldehyde was added at 40° C., and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0212] (Comparative Example 6)
[0213] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 50° C., 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 0.4 hours. The mixture was cooled to 40° C., 145 g of n-butylaldehyde was added, and the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0214] (Comparative Example 7)
[0215] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 70° C., 200 g of hydrochloric acid with a concentration of 35% by weight was added, and the mixture was kept for 3 hours. The mixture was cooled to 60° C., 160 g of n-butylaldehyde was added, and the mixture was kept at 60° C. for 3 hours to perform acetalization reaction, and then the reaction was terminated, and the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0216] (evaluate)
[0217] The polyvinyl acetal resins obtained in Examples and Comparative Examples were evaluated as follows.
[0218] (1) Evaluation of polyvinyl acetal resin
[0219] (1-1) Acetal group content, hydroxyl group content, acetyl group content
[0220] The obtained polyvinyl acetal resin was analyzed using an AV400 spectrometer (manufactured by Bruker). 1 The amount of acetal groups, the amount of hydroxyl groups and the amount of acetyl groups were calculated by H-NMR measurement.
[0221] It should be noted that the obtained polyvinyl acetal resin was dissolved in DMSO-D6 so as to be 1.6 wt % to prepare a measurement solution. 1 H-NMR measurement was performed at 80°C.
[0222] (1-2) Ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin (ratio of the three-sequence hydroxyl structural unit)
[0223] The obtained polyvinyl acetal resin was analyzed using an AV400 spectrometer (manufactured by Bruker). 13 C-NMR measurement is performed to measure the ratio of the peak integrated value of the triad unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin. The details of the peak integrated value measurement are as described above.
[0224] The obtained polyvinyl acetal resin was dissolved in DMSO-D6 so as to be 12 wt % to prepare a measurement solution. 13 C-NMR measurement was performed at 80°C.
[0225] It should be noted that the polyvinyl acetal resin obtained in Example 11 was subjected to 13 C-NMR measurement was performed to measure the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups. The obtained measurement data are shown in Figure 1 .
[0226] (1-3) Average molecular weight determination
[0227] 0.04 g of the obtained polyvinyl acetal resin was added to 20 g of tetrahydrofuran, stirred and dissolved to prepare a resin solution. The resin solution was measured by gel permeation chromatography using LF-804 (manufactured by SHOKO) as a column to determine the weight average molecular weight (Mw) and number average molecular weight (Mn) based on polystyrene conversion. In addition, Mw / Mn was calculated based on the obtained Mw and Mn.
[0228] (1-4) Viscosity measurement
[0229] The obtained polyvinyl acetal resin was dissolved in an ethanol-toluene mixed solution at a weight ratio of 1:1 so as to be 5% by mass to prepare a sample for viscosity measurement. The viscosity of the obtained sample for viscosity measurement was measured using a B-type viscometer.
[0230] In addition, as a B-type viscometer, a TVB-10 type viscometer (manufactured by Toki Sangyo Co., Ltd.) was used, and the rotation speed and the rotor were set as follows for measurement.
[0231] Examples 1 to 14, 17, Comparative Examples 1, 4 to 7: Rotation speed 30 rpm, SPINDLE No. M1 Example 16, Comparative Example 2: Rotation speed 30 rpm, SPINDLE No. M2
[0232] Example 15, Comparative Example 3: Rotation speed 60 rpm, SPINDLE No. M1
[0233] (1-5) High performance liquid chromatography [HPLC] determination
[0234] The polyvinyl acetals obtained in Examples and Comparative Examples were prepared by adjusting the concentration to 0.2 mg / mL using THF / IPA = 7 / 3 [volume ratio] as a solvent to prepare measurement samples.
[0235] As the HPLC apparatus, "Prominence" manufactured by Shimadzu Corporation was used; as the LC column, "XBridge BEH C18 (inner diameter 2.1 μm×10 cm, filler particle size 3.5 μm)" manufactured by Waters was used; and as the evaporative light scattering detector, "ELSD_LTII" manufactured by Shimadzu Corporation was used.
[0236] The analysis was carried out according to the following steps. Water was used as mobile phase A, and THF / IPA=7 / 3 [volume ratio] was used as mobile phase B. At the moment before the sample was injected, the interior of the column of the HPLC system was filled with a mixed solvent of mobile phase A / mobile phase B at a volume ratio of 9 / 1. The sample was injected in this state, and the proportion of mobile phase B in the mobile phase was increased at a constant rate (4.5 vol% / min) over 20 minutes from the injection of the sample. Only mobile phase B flowed for 10 minutes starting from 20 minutes after the injection. The column temperature was 45°C, and the liquid delivery rate was 0.4 mL / min.
[0237] It should be noted that the polyvinyl acetal resin obtained in Example 5 was subjected to HPLC measurement, and the obtained measurement data (vertical axis: peak intensity, horizontal axis: retention time [RT]) are shown in FIG. Figure 2 .
[0238] [Calculation of half-value width]
[0239] Peak half-value width W 0.5h The peak width at the 50% peak height position was measured by reverse phase partition gradient HPLC under the above conditions. The data actually obtained were analyzed using "Labsolutions LC (ver.5.7.1SP1)" manufactured by Shimadzu Corporation under the following conditions.
[0240] Width: 100 seconds
[0241] Slope: 200μm
[0242] Drift: 0μV / min
[0243] T.DBL: 1000 minutes
[0244] Minimum area / height: 10000 counts (Japanese: カウント)
[0245] The peak 50% height width calculated during analysis under these conditions is defined as W. 0.5h And calculate.
[0246] (2) Evaluation of Slurry Composition for Ceramic Green Sheet [Viscosity Stability over Time]
[0247] (Preparation of Inorganic Powder Dispersion)
[0248] 1 part by weight of polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., BL-1) was added to a mixed solvent of 20 parts by weight of toluene and 20 parts by weight of ethanol, and the mixture was stirred and dissolved. Next, 100 parts by weight of barium titanate powder (manufactured by Sakai Chemical Industry Co., Ltd., BT01) was added to the resulting solution, and the mixture was stirred for 180 minutes using a bead mill (Readymill manufactured by IMEX Corporation), thereby preparing an inorganic powder dispersion.
[0249] (Preparation of resin solution)
[0250] 8 parts by weight of a polyvinyl acetal resin and 2.1 parts by weight of a plasticizer (G260 manufactured by Sekisui Chemical Co., Ltd.) were added to a mixed solvent of 45 parts by weight of ethanol and 45 parts by weight of toluene, and stirred and dissolved to prepare a resin solution.
[0251] (Preparation of slurry for ceramic green sheets)
[0252] The resin solution was added to the obtained inorganic powder dispersion, and the mixture was stirred for 90 minutes using a bead mill to obtain a slurry composition for ceramic green sheets.
[0253] (2-1) Viscosity stability over time
[0254] The viscosity of the obtained slurry composition for ceramic green sheets was measured at 20°C and a rotation speed of 1.0 (1 / s) using a rheometer (Discovery HR 10 manufactured by TA Instruments). In addition, the viscosity of the slurry composition for ceramic green sheets after being placed at 23°C for one week was also measured under the same conditions, and the viscosity change rate before and after one week was calculated. The obtained viscosity change rate was evaluated according to the following criteria.
[0255] AA: Viscosity change rate is less than 400%
[0256] A: Viscosity change rate is more than 400% and less than 500%
[0257] B: Viscosity change rate is more than 500% and less than 600%
[0258] C: Viscosity change rate exceeds 600%
[0259] (3) Evaluation of ceramic green sheets
[0260] (Production of ceramic green sheets)
[0261] The obtained slurry was applied on a release-treated PET film using a coater so as to have a thickness of 20 μm after drying, and then heated and dried to produce a ceramic green sheet.
[0262] (3-1) Tensile strength
[0263] The obtained ceramic green sheet was subjected to the measurement of the breaking stress (MPa) at a tension rate of 20 mm / min at 23°C using a tensile testing machine (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-J) in accordance with JIS K 7113. 30 test pieces were prepared, and the measurement was performed 30 times. The average breaking stress was calculated and evaluated according to the following criteria.
[0264] AA: Breaking point stress exceeds 32MPa
[0265] A: The breaking point stress exceeds 30MPa and is below 32MPa
[0266] B: The breaking point stress exceeds 25MPa and is less than 30MPa
[0267] C: Breaking point stress is below 25MPa
[0268] (3-2) Deviation of tensile strength
[0269] The obtained ceramic green sheet was subjected to the measurement of the breaking stress (MPa) at 23°C and a tensile speed of 20 mm / min using a tensile testing machine (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-J) in accordance with JIS K 7113. Thirty test pieces were prepared, and the measurement was performed 30 times. The standard deviation of the breaking stress was obtained and evaluated according to the following criteria.
[0270] AA: Standard deviation of stress at breaking point is 0.40 or less
[0271] A: The standard deviation of the breaking point stress is more than 0.40 and less than 0.50
[0272] B: The standard deviation of the breaking point stress is more than 0.50 and less than 0.60
[0273] C: The standard deviation of the stress at the breaking point exceeds 0.60
[0274] [Table 1]
[0275]
[0276] [Table 2]
[0277]
[0278] Industrial Applicability
[0279] According to the present invention, it is possible to provide a polyvinyl acetal resin which, when used as a binder for a ceramic green sheet, can provide a ceramic green sheet having uniform tensile strength and high stress at break.
Claims
1. A polyvinyl acetal resin, wherein the polyvinyl acetal resin is 13 The ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the following formula (a) obtained by C-NMR measurement, i.e., nuclear magnetic resonance measurement, to the total peak integral value of the methine C atom represented by (a)', (b)', and (c)' in the triple unit represented by the following formula (a), the following formula (b), and the following formula (c) is less than 0.23, The weight average molecular weight of the polyvinyl acetal resin is greater than 230,000. In high performance liquid chromatography (HPLC) measurement, the half width of the peak observed within the retention time range of 20 minutes to 30 minutes is 0.50 or less, In the formula (b) and the formula (c), R is each independently hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
2. The polyvinyl acetal resin according to claim 1, wherein the solution viscosity is 30 mPa·s or more and 600 mPa·s or less when a 5 mass % solution of the polyvinyl acetal resin dissolved in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C. 3 . The polyvinyl acetal resin according to claim 1 , wherein the amount of hydroxyl groups is 23 mol % or more and 40 mol % or less. The polyvinyl acetal resin according to any one of claims 1 to 3, wherein the amount of acetyl groups is 0.1 mol% to 5 mol%. The polyvinyl acetal resin according to any one of claims 1 to 4, which has a molecular weight distribution of 2.75 or less. The polyvinyl acetal resin according to any one of claims 1 to 5, which is used for a ceramic green sheet. 7 . A slurry composition for ceramic green sheets, comprising the polyvinyl acetal resin according to claim 1 , an organic solvent, and a ceramic powder. 8 . A ceramic green sheet obtained by using the slurry composition for ceramic green sheets according to claim 7 . 9 . A multilayer ceramic capacitor obtained by using the ceramic green sheet according to claim 8 .
